(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The polity of our country has realized thesignificance of the development of weaker sections specially the scheduledcastes since Independence. Consequently, planned efforts have been made fortheir upliftment by the government. This paper has examined the progress madewith regard to their social (health, housing, workforce participation,availability of basic amenities and wage employment under income generationschemes), educational and occupational status. Based on secondary data, it hasbeen found that no doubt, a positive change on various socio-economicparameters has been recorded but, that change has touched merely less than halfof their population. Further, the gap between the mainstream and scheduledcaste population still persists significantly in our traditional society.Therefore, there is an urgent need to reorient and focus the strategy in orderto support the lesser privileged by providing qualitative education andinfusing among them the individualistic and moralistic values of self-denial, temperance,forethought, thrift, sobriety and self-reliance essential to bring thesedowntrodden into the national mainstream. With the noble intention of self-employment,resulting in reducing the unemployment and poverty among the backward classes,government of Maharashtra established BackwardClass Development Corporation Ltd., in the year 1978, recently the aboveinstitution completed 30 years of its services. The social strata which isknown as the backward class represents the down trodden classes of the society.BC has its origin in the ancient Indian social system. The ancient Indiansocial systems divides the society into four broad classes namely the Brahmin,the warrior class, the serving class in addition to this fifth class known aswho were untouchable existed in ancient India. With a view of socialisticpattern of society as mentioned in the constitution of India along with thebasic principles of equity, fraternity, freedom and justice for all Governmentat Central and State levels established corporations which meant to work asagents of economic development of the backward classes by providing finance tothem. Corporations are playing very dominant role for the development of backward classes by providing finance and creating self-employment opportunitiesfor the backward classes.